Effect of Electroacupuncture on Inhibition of p38 MAPK Pathway on Neuromotor Function in Rats with Spinal Cord Injury - Wei CHEN; Yaochi WU (康复学报)
Objective:To observe the effect of electroacupuncture on neuromotor function of rats with spinal cord injury, and to explore its mechanism based on p38 MAPK pathway.Methods:A total of 63 adult male SD rats were randomly divided into sham group, SCI group and SCI-EA group, with 21 cases in each group.The spinal cord was not injured in Sham group, the SCI group and SCI-EA group were established by crushing the spinal cord with external force.The sham group and SCI group did not take any intervention, At the second day after operation, SCI-EA groupwas treated by electro-acupuncture instrument (continuous wave, frequency 2 Hz, intensity 1 mA), The needling site was T10Jiaji acupoint, 30 minutes per time, once a day, resting every 5 days, continuous treatment for 28 days.Spinal cord injury behavioral score (BBB) was used to evaluate the changes of motor function after spinal cord injury; apoptosis of spinal cord neurons was detected by TUNEL method; Caspase-3 positive cells in spinal cord tissue were detected by immunohistochemical SP method;and protein expression was detected by Western blot.Results:Compared with SCI group, BBB score of SCI-EA group was significantly higher after EA intervention for seven days, with statistically significant differences (P<0.05); Caspase-3 positive cells in spinal cord tissue of SCI-EA group were significantly lower, and the number of apoptotic cells reduced significantly, The positive expression of p38 MAPK and iNOS decreased significantly, with statistically significant differences (P<0.05).Conclusion:Electroacupuncture can inhibit the activation of p38 MAPK and iNOS pathway after spinal cord injury, reduce the apoptosis of spinal cord neurons, and improve the neuromotor function of spinal cord injury rats.